Modelling of the Simultaneous Saccharification and Fermentation for a Pine Sawdust Biorefinery - Mendieta, Carolina Monica (2022)
The decline in world oil reserves evidences the need to diversify the sources of equivalent raw materials. The use of biomass is one of the most explored alternatives. This work evaluates the second-generation bioethanol (2G) production from a pine sawdust soda-ethanol pulp by simultaneous hydrolysis and fermentation (SSF) to obtain the best conditions for scaling up the process. Experimental designs have been used to find mathematical models that define the complex situation jointly varying time with other variables (enzyme load and temperature). Time periods in the full model varied from 0 h to 72 h. Given the results (curve shape differences), it was decided to split the design in two, covering periods from 0 h to 24 h (Model I) and from 24 to 72 h (Model II). The pulp chemical composition was 80.2% glucans, 7.2% xylans, 0.3% galactans, 8.4% mannans, 3.7% lignin. Cellic® Ctec2 cellulolytic enzymes were used for saccharification and Saccharomyces cerevisiae IMR 1181 (SC 1181) yeast for fermentation. The best conditions found in the two designs were 30 FPU g−1 glucans, 39°C, 24 h for Model I, and 30 FPU g−1 glucans, 35°C, 72 h for Model II. Fermentation optimal values were 63.23 and 81.93 for Models I and II, respectively.